Antiulcer Effect of Senna multiglandulosa via Increased Secretion of Mucus and Nonprotein Sulfhydryl Groups in an Experimental Murine Model. (12th August 2022) - Palomino-Pacheco, Miriam; Rojas-Armas, Juan Pedro; Arroyo-Acevedo, Jorge Luis; Ortiz-Sánchez, José Manuel; Justil-Guerrero, Hugo Jesús; Cieza-Macedo, Edwin César; Ramos-Cevallos, Norma; Alshahrani, Mohammed Merae; Mahmud, Shafi; Herrera-Calderon, Oscar
Abstract : Peptic ulcer is a universal condition that is a public health problem due to its prevalence, risk of complications and socioeconomic impact. This study aimed to determine the antiulcer effect of the hydroalcoholic extract from Senna multiglandulosa leaves against ethanol-induced gastric ulcer in rats. Thirty-six male albino Holtzman rats were assigned to six groups. Group I received physiological saline (PS) at doses of 10 mL/kg; group II: ethanol (PS + ethanol 5 mL/kg); group III; omeprazole 100 mg/kg/day (gold standard); groups IV, V and VI received doses of 100, 250 and 500 mg/kg/day of S. multiglandulosa extract, respectively. The stomach was removed to determine the ulcerative lesions and two sections of the glandular zone to carry out the analysis of the gastric mucus and sulfhydryl groups content. As result, S. multiglandulosa at doses of 250 and 500 mg/kg produced a significant decrease of the injured area, with values of 46.28 ± 7.95 mm 2 and 6.91 ± 2.48 mm 2, respectively (P < 0.001 ). The protective effect was showed at dose of 500 mg/kg (92.27%) and a significant increase in the production of mucus with a value of 83.13 ± 13.09 mg/mL/g of tissue (61.14%). The production of nonprotein sulfhydryl groups (NP-SG) also increased significantly at the three evaluated doses, being 250.34 ± 21.16  μ g/g tissue at dose of 500 mg/kg (119.94%). It is concluded that S. multiglandulosa extract protected against ethanol-induced gastric ulcer due to increased gastric mucus secretion and its antioxidant activity due to the generation of nonprotein sulfhydryl groups.